ANALISIS KINERJA PEMUNGUTAN DAN RETRIBUSI PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH KOTA BATAM - Baru Harahap; Syahril Effendi (Universitas Putera Batam, 2020)
This study aims to find answers to the level of advertisement tax collection performance in the city of Batam, and its contribution to local tax revenue. This research applies a descriptive analysis method, The object of this study is Batam City. The sampling technique used is non-probability sampling, that is the technique of determining the sample using certain considerations or by using financial statements from 2015 to 2019. The results of hypothesis testing using multiple regression analysis methods show that the performance of the collection and retribution of advertisement tax levies on Batam City Dispenda has a significant effect on the local revenue. While partially the performance of collection on the Batam City Dispenda has a significant relationship to the original revenue of the region, however, advertisement tax levies have a significant effect on the region's original revenue on the Batam City.